Outcomes of Tension Band Fixation in Olecranon Fractures and Osteotomies With Sutures: A Metal-free Solution. Issue 3 (14th September 2021) - Thiruvasagam, Vetri G.; Shah, Nasir; Sanger, Rajiv; Robb, Curtis; Badge, Ravi
Abstract : To restore the extensor function of the elbow, tension band wiring is a commonly used technique in managing stable olecranon fractures and osteotomies with excellent results. However, the outcome and patient satisfaction are marred with high rates of hardware-related complications requiring reoperation. To diminish the risk of these complications, we employed sutures for tension band fixation instead of wires in open reduction and internal fixation of Mayo types IA and IIA olecranon fractures and olecranon osteotomies in 15 of our patients. All patients achieved the radiologic union of the fractures and osteotomies by 12 weeks, except for 1 patient who developed fibrous union at the osteotomy site. None of the patients had any functional limitations at discharge and had good to excellent outcomes on the Mayo Elbow Performance Score. There were no complications related to hardware and the need for reoperation. The use of sutures in tension band fixation of olecranon fractures and osteotomies replicates the results of the highly successful technique of tension band wiring while significantly reducing the hardware-related complications.